Sandfly’s (Diptera: Psychodidae: Phlebotominae: Lutzomyia) taxonomic diversity in a leishmaniasis endemic zone in northern Colombia - Ardila, Marlon Mauricio (2022)
The Montes de María region is one of the most important leishmaniasis macro hotspots in Colombia, with the municipality of El Carmen de Bolívar stands out for having high prevalence rates of visceral leishmaniasis. This municipality has fragments of tropical dry forest with abundant wildlife, incriminated as reservoirs of Leishmania and affected by fruit tree crops, providing optimal ecological conditions for the circulation of some phlebotomine sandflies species with epidemiological antecedents. Recently, 20 species of Lutzomyia were recorded for this municipality, which added to the presence of Lu. evansi, vector of L. infantum chagasi, etiologic agent of visceral leishmaniasis and Lu. gomezi and Lu. panamensis, vectors of L. braziliensis and L. panamensis, etiological agents of cutaneous leishmaniasis. As an aim, it was proposed to analyze the spatiotemporal variation of phlebotomine assemblage in El Bledo, El Carmen de Bolívar, a leishmaniasis endemic area in northern Colombia.